FOREST FRAGMENT IN THE MUNICIPAL SPRING OF ITAPIRA-SP FAVORS CARBON NEUTRALIZATION MITIGAGING THE GREENHOUSE EFFECT - Martelli , Anderson (Journal of Interdisciplinary Debates, 2022)
Evidence of climate change that has occurred in recent years is largely attributable to anthropic influences. Excess carbon dioxide (CO2) in the atmosphere is harmful, being one of the substances responsible for climate change and trees favor the sequestration of this CO2. Thus, this article aimed to quantify the carbon that was neutralized in a forest fragment located at a spring in the municipality of Itapira-SP, mitigating the emission of greenhouse gases. The results showed that this fragment neutralized 261.20 tons of carbon over 20 years. Forests constitute important carbon stocks with the removal of atmospheric CO2 through the process of photosynthesis. The preservation of this forest fragment by the government and civil society characterize plausible actions with regard to the climate changes that the world has been experiencing.